Hidradenitis suppurativa and electrocardiographic changes: a cross‐sectional population study. (1st January 2018) - Juhl, C.R.; Miller, I.M.; Jemec, G.B.; Kanters, J.K.; Ellervik, C.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease, recently associated with metabolic syndrome, subclinical atherosclerosis and increased risk of cardiovascular disease. Objectives: To investigate the hitherto unknown electrocardiographic (ECG) changes associated with HS, which have recently been associated with significant cardiovascular burden. Methods: Data were obtained from the cross‐sectional Danish General Population Study (GESUS). HS diagnosis was based on a validated self‐reported questionnaire; 404 individuals met the HS diagnosis criteria and 19 001 controls without HS were identified. Severity of HS was staged according to a modified Hurley score. The ECG parameters of heart rate (HR), PR interval, QRS duration, JTc interval and QTc interval were obtained from 12‐lead resting ECGs. We investigated the difference in means by unpaired t ‐test or anova . Results: HR was significantly higher [mean difference 2·3 beats per min (bpm), 95% confidence interval (CI) 1·2–3·4; P < 0·01] when adjusting for age and sex, but when adjusting for multivariates, there was no significant difference (0·3 bpm, 95% CI –0·7 to 1·4; P = 0·52). Severe HS was significantly associated with increased HR across all models (2·9 bpm, 95% CI 0·7–5·1; P = 0·01). Mean QRS duration was significantly shorter in the group with mild HS but not in the groups with moderate and severe HS. Conclusions: Mean resting HR in patients with severe HS was significantly higher compared with controls. Given that resting HR is associated with increased risk of all‐cause and cardiovascular mortality, and that patients with HS have increased risk of cardiovascular events, this finding is potentially important, easily testable and intervenable.